The Impact of Educational Quality on Student Satisfaction: The Role of Student Experience in Postgraduate Education - Pramono, Suwito Eko; Yulianto, Arief; Nasrun, Nasrun; Wijaya, Angga Pandu (Journal of Educational Review and Research, 2025)
This study aims to examine the influence of educational quality on student satisfaction through student experience among postgraduate students at public universities. Few studies have focused specifically on the learning experience of postgraduate students, indicating the need for further research in this area. This study employs a quantitative approach with a causal research design. Data were collected through a survey of 213 postgraduate students from public universities selected using purposive sampling. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results show that educational quality has a significant effect on student experience, and student experience significantly affects student satisfaction. Furthermore, student experience was found to mediate the relationship between educational quality and student satisfaction. This study highlights the importance of student experience for postgraduate students. The implications emphasize the need for higher education institutions to improve the technical aspects of educational quality such as learning resources and facilities as well as technology infrastructure to enhance the learning experience of postgraduate students